New species and new records of chewing lice (Phthiraptera: Amblycera and Ischnocera) from bulbuls (Passeriformes: Pycnonotidae) in Vietnam - Najer, Tomas; Sychra, Oldrich; Hung, Nguyen Manh; Capek, Miroslav; Podzemny, Petr; Literak, Ivan (Zootaxa, 2012)
Seven species of chewing lice (Insecta: Phthiraptera) were found on five species of bulbuls (Passeriformes: Pycnonotidae)in northern Vietnam. Three new species of the genera Brueelia and Philopteroides are described; they and their type hostsare: Brueelia flavala ex Hemixos flavala Blyth, 1845 B. cucphuongensis ex Pycnonotus finlaysoni Strickland, 1844 andPhilopteroides flavala ex Hemixos flavala Blyth, 1845. First records of chewing lice from Hemixos castanonotus Swin-hoe, 1870 and Iole propinqua (Oustalet, 1903), and a new host record for Myrsidea ochracei and Sturnidoecus sp. are also included.